Pengaruh ESG Disclosure terhadap Return Saham pada Perusahaan Jakarta Islamic Index (JII) Periode 2020–2024 - Azza Ibraisama Ersyada; Sunarsih Sunarsih (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
The growing integration of sustainability considerations into investment decisions raises a fundamental empirical question: does ESG disclosure systematically translate into superior equity returns, particularly within Shariah-compliant markets? This study examines the effect of ESG Disclosure Index on stock returns among 12 companies listed in Jakarta Islamic Index (JII) during 2020–2024, yielding 60 balanced panel observations. ESG scores were constructed through content analysis of sustainability reports using a 45-item checklist based on GRI Standards 2021 and POJK 51/2017, covering environmental, social, and governance dimensions. Three control variables were added: ROA, Leverage, and Firm Size (SIZE). The Common Effect Model with HC1 Robust Standard Errors was selected based on Chow Test [F(11,44)=1.095; p=0.387], LM Test [χ²(1)=1.457; p=0.227], and Hausman Test [χ²(4)=8.040; p=0.090]. Results show a negative but statistically insignificant effect of ESG disclosure on stock return (β=−2.688; p=0.257; Adj R²=0.059), rejecting H1. None of the control variables significantly influenced returns. The non-significance reflects six structural factors: regulatory immaturity of POJK 51/2017 (effective 2019), dominance of short-term retail investors, high ESG score homogeneity within JII constituents (std=0.084), macro-economic distortions during COVID-19, long-term nature of ESG benefits, and pre-publication information internalization. These findings are consistent with evidence from other emerging Islamic markets (Atan et al., 2018; Hambali & Adhariani, 2023; Aydogmus et al., 2022).